KAJIAN BANJIR DI SUB DAS BATI-BATI DAS MALUKA KABUPATEN TANAH LAUT - Saidatul Ummah; Syarifuddin Kadir; Dina Naemah (Universitas Lambung Mangkurat, 2022)
Flooding has the potential to pose a danger to the human life and environment, and so it is necessary to conduct a flood study. This study have a purpose to identify the frequency of floods and determine the direction of flood recovery qualification in sub-watershed Bati-Bati Maluka Watershed Tanah Laut Regency. Village selection is done Purposive sampling which is a village that often experiences flood events, 6 villages in two sub-districts with the number of respondents as many as 80 respondents. Data analysis was conducted to establish the classification of watersheds in the research area, namely flood frequency data obtained from flood disaster event reports and direct observations. Then, the results of the study are presented in a descriptive analysis. The study of flood events in sub-watershed Bati-Bati Maluka Watershed Tanah Laut is the frequency of floods that occur in Bati-Bati subdistrict occurs flooding 1 time in a period of 2 years, with the duration of flooding that occurs is < 1 month and the average height of flood inundation 0.5 -1 meter. Meanwhile, in Kurau sub-district flooded once in a period of 2 years, with the duration of the flood that occurred is 1-2 months and the average height of flood puddles 0.5 - 1 meter. Recovery qualifications in Bati-bati and Kurau subdistricts are needed which can be done with two programs, namely long and short termBanjir dapat berpotensi menimbulkan kerusakan terhadap kehidupan manusia dan lingkungan, sehingga kajian banjir perlu dilakukan. Tujuan dari penelitian ini ialah untuk mengidentifikasi frekuensi banjir serta menentukan arahan kualifikasi pemulihan banjir di Sub DAS Bati-Bati DAS Maluka Kabupaten Tanah Laut. Pemilihan desa untuk lokasi penelitian dilakukan dengan metode Purposive sampling yaitu desa yang sering mengalami kejadian banjir, 6 desa di dua Kecamatan dengan jumlah responden sebanyak 80 responden. Analisis data dilakukan untuk menetapkan klasifikasi DAS di wilayah penelitian dengan pengamatan langsung untuk mengetahui data frekuensi banjir yang diperoleh dari laporan kejadian bencana banjir. Kemudian, hasil penelitian disajikan secara analisis deskriptif. Kajian Kejadian Banjir Di Sub DAS Bati-Bati DAS Maluka Kabupaten Tanah Laut ialah frekuensi banjir yang terjadi di Kecamatan Bati-Bati terjadi banjir 1 kali dalam kurun waktu 2 tahun, dengan lama banjir yang terjadi yaitu < 1 bulan dan rata-rata tinggi genangan banjir 0,5 – 1 meter. Sedangkan, di Kecamatan Kurau banjir 1 kali dalam kurun waktu 2 tahun, dengan lama banjir yang terjadi yaitu 1 – 2 bulan dan rata-rata tinggi genangan banjir 0,5 - 1 meter. Kualifikasi Pemulihan di Kecamatan Bati-bati dan Kecamatan Kurau yang diperlukan ialah sedang yang dapat dilakukan dengan dua program yaitu jangka panjang dan jangka pendek.